Productivity, profitability and efficiency of diversified rice-based farming systems in the transmigration villages of Rasau Jaya District in West Kalimantan, Indonesia - Dewi, D. O.; Mendoza, T. C. (2006)
Different diversification schemes are practiced by farmers in the different transmigrant villages of Rasau Jaya District, West Kalimantan, Indonesia. To identify the scheme that best satisfies the farm household goals of food security and continuous cash flows on a sustainable basis, 380 farmers were interviewed using both informal and formal survey methods. Raising annual crops and animals was the most common diversification scheme practiced by 75% of the farmers. Only 24% of the farmers were into annuals + perennials + animals and only very few were into annual crops alone or a combination of annuals and perennials. Ten (10) diversification schemes were practiced by 62% of the farmers and they were evaluated based on various measures of productivity, profitability and efficiency. Crop yields, total farm productivity, land use efficiency and net income were highest in the diversification scheme involving Rice + Corn + Cow + Native Chicken (R+C+CW+NC) giving a total adjusted yield of 8.23 t/ha. The slack time of the farm household was fully utilized in this scheme which increased labor use efficiency. Rice yield was highest which led to its highest technical efficiency (TE= 0.86). This was due to the application of composted manure. Without applying composted manure, rice grown under submerged field conditions had low technical efficiency (TE= 0.32-0.44) due to its low yield (0.64-0.87 t/ha). This is because of the low availability of nutrients in the highly acidic peat soils (pH<5) of the district. To unlock the adsorbed nutrients, many farmers resorted to burning peat soils which needed spraying of herbicide to initially dry the thick weed biomass to facilitate burning. Integrating ruminants in rice-based farming systems as in R+C+CW+NC was found to be the diversification scheme that best satisfies the farm household goals of increased farm productivity, food security and continuous cash flows. This farming system could be the key that would make burning of peat soils impractical, thus, conserving the nutrient-rich peat soils of the transmigration villages of Rasau Jaya District, West Kalimantan, Indonesia for long-term productivity.
Keywords: Rice farming -- Indonesia